PENGARUH PEMBIAYAAN MUDHARABAH TERHADAP PROFITABILITAS BANK SYARIAH PERIODE 2015- 2020 (Studi Pada PT Bank Syariah Mandiri) - Widya Puspita Sari (COMPETITIVE, 2022)
This study aims to determine and also to analyze the effect of mudharabah financing on profitability. This type of research is a causal associative research. The research population used is public financial reports. The data analysis technique used is quantitative data by performing statistical analysis using the classical assumption test analysis, hypothesis testing using t-test. The results showed that there was an influence between mudharabah financing and profitability as evidenced by the calculation. The conclusion is that mudharabah financing can affect the level of profitability at Bank Mandiri Syariah.